Kanker dan Gizi: Tinjauan Literatur - Podojoyo, Podojoyo; Hartati, Yuli; Purnama, Fajriah; Mangunsong, Sonlimar (Jurusan Gizi, Poltekkes Kemenkes Palembang, 2025)
Cancer remains a leading cause of death worldwide, with over 18 million new cases and nearly 10 million cancer-related deaths each year. As our understanding of cancer advances, the critical role of nutrition in cancer prevention, progression, and management has become increasingly evident. This review explores the multifaceted relationship between diet and cancer, focusing on the mechanisms through which dietary factors can influence cancer risk, including inflammation, oxidative stress, and metabolic pathways. Additionally, it highlights the impact of various nutrients and bioactive compounds found in foods, such as vitamins, minerals, and phytochemicals, on cancer prevention and therapy. The review also examines the importance of managing food-drug interactions in cancer treatment, particularly with chemotherapy, targeted therapies, and immunotherapies, where metabolic enzymes, such as cytochrome P450, play a significant role. By synthesizing the latest research, this review emphasizes the need for personalized nutrition strategies to optimize cancer care and improve treatment outcomes, underscoring the potential of nutrition as an integral part of cancer prevention and therapy.